Aggregation-induced intersystem crossing: a novel strategy for efficient molecular phosphorescence. Issue 40 (30th August 2016) - Yang, Li; Wang, Xijun; Zhang, Guozhen; Chen, Xiaofeng; Zhang, Guoqing; Jiang, Jun
Abstract : "Aggregation-induced intersystem crossing" reduces the energy gap to promote the ISC rate and phosphorescence enhancement. Abstract : "Aggregation-caused quenching" (ACQ) and "aggregation-induced emission" (AIE) are two well-known mechanisms for polymer luminescence. Here we proposed an alternative mechanism termed "aggregation-induced intersystem crossing" (AI-ISC). By aggregating certain fluorescent dye molecules, one can improve the energy matches between excited singlet and triplet states so as to promote the intersystem crossing (ISC) rate, and consequently prolong the lifetime of excited electrons by steering them into triplet states. First-principles calculations suggested that the enhanced ISC rate could substantially promote molecular phosphorescence in aggregated systems of originally fluorescent dye molecules, as later validated by experimental measurement. Meanwhile, the emission spectra experience a red shift along with the aggregation, providing a convenient knob to tune the phosphorescence wavelength. The proposed AI-ISC mechanism may open up a new design approach for the emerging luminescent material applications.